CONTEMPT OF COURT IN INDONESIAN REGULATION - Opik Rozikin (CIC Lembaga Riset dan Konsultan Sosial, 2019)
Abstract: Contempt of court is often an interesting topic of discussion, one of which is in the national legal development program, this is inseparable from the rampant phenomenon of actions that are considered to injure the authority of the judicial institutions in Indonesia. The provisions of the contempt of court that were previously foreign indeed contained in the explanation of Law No. 14 of 1985 concerning the Supreme Court paragraph 4 paragraph 4 does not meet the expectations of the Indonesian people, because there is no follow up and more concrete arrangements regarding the Contempt of Court. Whereas the idea of ​​forming a law concerning the Contempt of Court has become part of the 2002 legal policy mandated by Law No. 25 of 2000 concerning the National Law Development Program. The Indonesian criminal justice system is included in the Non Adversary Model system. Judges have broad responsibilities in carrying out the trial process. Contempt of court arrangements are spread in the Criminal Code, Criminal Procedure Code, and several laws and regulations in Indonesia. Abstrak: Contempt of court sering menjadi bahan perbincangan menarik, salah satunya dalam program pembangunan hukum nasional, hal ini tidak terlepas dari maraknya fenomena tindakan yang dianggap mencederai kewibawaan institusi peradilan di Indonesaia. Ketentuan Contempt of Court yang dahulu asing memang telah termuat dalam penjelasan Undang Undang No. 14 Tahun 1985 Tentang Mahkamah Agung butir 4 alinea ke-4 tidak sesuai dengan harapan bangsa Indonesia, dikarenakan tidak ada tindak lanjut dan pengaturan yang lebih konkret tentang Contempt of Court tersebut. Padahal ide pembentukan undang undang tentang Contempt of court ini, telah menjadi bagian dari kebijakan hukum tahun 2002 sebagaimana yang diamanahkan Undang Undang No. 25 Tahun 2000 tentang Program Pembangunan Hukum Nasional. Sistem peradilan pidana Indonesia termasuk kedalam sistem Non Adversary Model. Hakim memiliki tanggung jawab yang luas dalam menjalankan proses persidangan. Pengaturan Contempt of court tersebar dalam KUHP, KUHAP, dan beberapa peraturan perundang-undangan di Indoneisa.